Dementia with Lewy bodies: A differential diagnosis of normal pressure hydrocephalus: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Durand, Hélène; Baloglu, Seyyid; Bilger, Mathias; Ollivier, Irène; Cretin, Benjamin; Anheim, Mathieu; Proust, François; Blanc, Frédéric; Philippi, Nathalie
Abstract: Background: The diagnosis of idiopathic normal pressure hydrocephalus (NPH) is challenging and remains overestimated because of the absence of specific clinical, imaging or biological features. It relies on association of classical triad of symptoms (gait disturbance, cognition impairment, urinary symptoms) associated to a ventricular enlargement. Several differential diagnoses should be considered with an initial presentation suggestive of NPH, such as dementia with Lewy bodies (DLB), Alzheimer disease (AD) and vascular dementia (VD). The aim of this study was to identify NPH differential diagnosis as well as to highlight clinical and radiological features that could help questioning this diagnosis, before performing invasive procedures. Method: In this monocentric retrospective study, we included 42 patients fulfilling the criteria of possible NPH on initial presentation. At the end of the follow‐up, we classified the sample into patients with probable NPH (NPH group ; n = 13), differential diagnosis of NPH (NPH‐ group; n = 21) and dual pathology with criteria of probable NPH (NPH+; n = 8), depending on their outcome after cerebrospinal fluid (CSF) drainage. We collected clinical data, including results of cognitive assessment, as well as results of CSF biomarkers, EEG, functional and morphological neuroimaging. Ventricular enlargement profile was analyzed using different visual measures on MRI. Result: The main differential diagnosis of NPH was DLB (21/21), mixed with vascular dementia in four cases. None of the patient had a CSF profile suggestive of AD. Regarding clinical features, asymmetric parkinsonism, fluctuations, agitation during sleep, visual hallucinations and visuospatial impairment were significantly more frequent in NPH‐ patients, compared to NPH patients (p=0.033). The callosal angle was significantly more acute (<104° ; p <0.01) and fourth ventricular dilatation greater (>17 mm ; p<0.01) in NPH patients than in NPH‐ patients, while there was no significant difference in the dilatation of lateral ventricles and third ventricle. Conclusion: DLB appeared as the main differential diagnosis of NPH. Our results indicate that the existence of asymmetric parkinsonism, fluctuations, agitation during sleep, visual hallucinations or visuospatial impairment, as well as the absence of acute callosal angle or fourth ventricular dilatation should lead to consider DLB as a differential diagnosis of NPH.